2022-RA-934-ESGO Vaginal changes, sexual functioning and distress of women with locally advanced cervical cancer treated in the EMBRACE vaginal morbidity sub-study. (20th October 2022) - Suvaal, Isabelle; Kirchheiner, Kathrin; Nout, Remi; Sturdza, Alina; van Limbergen, Erik; Lindegaard, Jacob; Putter, Hein; Jürgenliemk-Schulz, Ina; Chargari, Cyrus; Tanderup, Kari; Pötter, Richard; Creutzberg, Carien; et al.
Abstract : Introduction/Background: The EMBRACE Vaginal Morbidity sub-study prospectively evaluated physician-assessed vaginal changes and patient-reported-outcomes (PRO) on vaginal and sexual functioning problems, and sexual distress in the first 2 years after radio(chemo)therapy with image-guided adaptive brachytherapy for locally advanced cervical cancer. Methodology: Eligible patients had FIGO 2009 stage IB2-IIIB cervical cancer with no or only limited (≤5 mm) vaginal involvement. Comprehensive assessment of vaginal changes was done before treatment, at 4–6 weeks and 3, 6, 12 and 24 months thereafter using CTCAE v3.0 and additional assessments. PRO were assessed at the same timepoints using validated Quality of Life (EORTC QLQ-C30 and CX24) and sexual questionnaires. Statistical methods included generalized linear mixed model analysis and Spearman's rho correlation coefficients. Results: 113 eligible patients were included. Over time, mild (grade 1) vaginal changes were reported in 10.8–36.8% of the participants. Of the 113 participants, 46.7% reported not being sexually active at 24 months, mostly because of losing interest in sex or lacking a partner. Among the sexually active women (41–54/113), 43.2–51.3% reported vaginal functioning problems starting at 4–6 weeks and more severe sexual problems and distress were reported by 5–15% of them. Significant differences ( p ≤.05) in physician-assessed vaginal morbidity were found between baseline and follow-up, without further clear changes. No or only small associations between vaginal changes and vaginal functioning problems and sexual distress were found. Conclusion: Relatively mild vaginal changes were reported after image-guided radio(chemo)therapy and brachytherapy according to EMBRACE-protocol. Vaginal functioning problems were reported by almost half of the sexually active women, while more severe problems and distress were reported by up to 15% of them. These results are favourable compared to previous data, potentially due to the combination of tumours with limited vaginal involvement and EMBRACE-specific treatment optimization and rehabilitation recommendations.